눈꺼풀 및 결막 종양으로 처음 발현된 급성 골수성 백혈병 - 김동주(Dong Ju Kim); 장민욱(Min Wook Chang) (Daihan angwa haghoi jabji, 2016)
목적: 급성 골수성 백혈병 환자에서 눈꺼풀 및 결막의 종양으로 처음 병발한 1예를 보고하고자 한다. 증례요약: 82세 남자 환자가 10일 전 발견된 양안 안구결막 및 위눈꺼풀의 덩어리를 주소로 내원하였다. 말초 혈액 검사에서 Hb 13.7 g/dL 백혈구 수는 5,530/mm3 (중성백혈구 74.4%, 임파구 10%, 단핵구 11.8%)로 특이소견을 보이지 않았다. 이밖에 동공의 대광반사, 외안근 운동, 안저 검사에서는 이상소견을 보이지 않았다. 양안 결막 및 우측 위눈꺼풀 병변에 대해 첫 내원 1주일 후 생검을 시행하였다. 이후 호흡곤란, 발열이 생겨 시행한 말초 혈액 검사에서 Hb 9.6 g/dL, 백혈구 수는 78,020/mm3 (중성구 0%, 임파구 7%, 단핵구 5%, 전골수세포 1%, 늦골수세포 4%, 골수세포 6%, 모세포 67%)의 소견이 나타났다. 생검에서 비전형적인 형질모양의 백혈병 세포의 침윤 소견이 보였다. 급성 골수성 백혈병 진단하에 항암화학요법을 시행하였으나, 폐렴 악화로 환자는 사망하였다. 결론: 말초 혈액 검사에서 특이소견이 보이지 않더라도 결막 및 눈꺼풀에 비특이적인 병변이 보일 시 급성 골수성 백혈병에서 선행한종양일 가능성을 염두에 두어야 한다. Purpose: To report a case of an 82-year-old male with acute myeloid leukemia presenting with bilateral isolated conjunctival and eyelid masses. Case summary: An 82-year-old male presented with a bilateral conjunctival mass and right eyelid mass occurring 10 days prior. He was diagnosed with prostate cancer 8 years ago and complete recovery was achieved using selective mass chemotherapy. He experienced a stroke 4 years ago and was treated using a carotid artery stent insertion and medication. In the initial laboratory test, hemoglobin was 13.7 g/dL and leukocyte count 5,530/mm3 (neutrophil 74.4%, lymphocyte 10%, monocyte 11.8%). Light reflex, movement of extraocular muscle and fundus examination were all normal. Biopsy was performed 1 week after the first visit. Seven days after biopsy, he complained of sudden dyspnea and febrile sense and was admitted to the intensive care unit via the emergency room (ER). The laboratory tests performed in the ER showed hemoglobin was 9.6 g/dL and leukocyte count was 78,020/mm3 (neutrophil 0%, lymphocyte 7%, monocyte 5%, promyelocyte 1%, metamyelocyte 4%, myelocyte 6%, blast 67%). The biopsy revealed diffuse proliferation of atypical plasmacytoid cells, consistent with leukemic infiltration. Under the diagnosis of acute myeloid leukemia, chemotherapy was administered. However, the patient died due to aggravated pneumonia. Conclusions: Even if non-specific findings appear on the peripheral blood tests, eyelid and conjunctival masses should be considered as possible tumors in acute myeloid leukemia. KCI Citation Count: 0